2021
DOI: 10.7860/ijars/2021/45463.2618
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Neurocortical Atrophy Scores on Imaging with Mini-Mental Status Examination

Abstract: Introduction: The term “Cognitive impairment” is used for decline of memory and behaviour, depicting its progressive nature, of which the most common cause is Alzheimer’s followed by vascular injury. Magnetic Resonance Imaging (MRI) and Mini-Mental State Examination (MMSE) together have an established role to identify aetiology and also to distinguish normal ageing from demented patients. Final diagnosis by brain biopsy is an invasive method, hence structural MRI scores are used to differentiate and characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…MTL atrophy and parietal lobe atrophy are specific for AD, whereas symmetric atrophy of frontal and temporal lobe favors frontotemporal dementia. [14] Another similar Indian study by Chatra et al, 2021, showed statistically significant association between Scheltens et al's imaging scores with MMSE. There is a moderately positive linear relationship between the two.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…MTL atrophy and parietal lobe atrophy are specific for AD, whereas symmetric atrophy of frontal and temporal lobe favors frontotemporal dementia. [14] Another similar Indian study by Chatra et al, 2021, showed statistically significant association between Scheltens et al's imaging scores with MMSE. There is a moderately positive linear relationship between the two.…”
Section: Discussionmentioning
confidence: 88%
“…This feature can be used as a screening tool in patients with subclinical dementia for early diagnosis and management. [16,17] MRI has many advantages as it is easy to perform, specific features help in diagnosing specific type of dementia which is crucial for the management, whereas molecular studies which are available for the diagnosis of AD are practically not available and cannot be used for the routine diagnosis in all patients because of logistical challenges. [18] MRI gives high resolution with excellent tissue contrast.…”
Section: Discussionmentioning
confidence: 99%